I-Takhrij: Inovasi Digital Dalam Pengajaran dan Pembelajaran Ilmu Takhrij Hadis - A. Irwan Santeri Doll Kawaid; Shumsudin Yabi; Syed Najihuddin Syed Hassan; Nur Afifi Alit; Mohd Fadzli Marhusin (Academic Inspired Network, 2026)
Tier 3